Education or business? - exhibition of human corpses - Wróbel, Grzegorz (Journal of Education, Health and Sport, 2017)
Exhibition "BODY WORLDS" which are presented exhibits of human remains are presented all over the world and are a major problem for the modern man, as presented on the preparations of the human not only serve scientific research, are not transferred to the medical schools to educate future doctors, but they were made available to the general public in the form of commercial and ambiguous. The aim of this study was to assess the ethical commercialization of human corpses "BODY WORLDS" exhibitions. Individual approach to the problems presented the dignity and value of human remains after death, of course, strongly related to the professed worldview. In the exhibits can be seen in both the scientific interest anatomical structures, as well as desecrated human remains or beautiful by its functional perfection of the body, understood also in terms of art. The question of ethics determines the right to decide for themselves, on the other hand, allows you to protect bodily integrity even after death. "BODY WORLDS" exhibition goes for the moral and ethical boundaries. In terms of people Gunther von Hagens for plastination of human remains which became a very profitable business, and its current activities defined as "plastination business" should be firmly said about the lack of moral principles.